Density and seismic velocity of hydrous melts under crustal and upper mantle conditions. (27th May 2016) - Ueki, Kenta; Iwamori, Hikaru
Abstract: We present a new model for calculating the density of hydrous silicate melts as a function of P, T, H2 O concentration, and melt composition. We optimize V P r, T r,   ∂ V / ∂ T,   ∂ V / ∂ P,   ∂ V 2 / ∂ T ∂ P, and K ′ of H2 O end‐member components in hydrous silicate melts, as well as K ′ of anhydrous silicate melts, using previously reported experimental results. The parameter set for H2 O end‐member component in silicate melt optimized in this study is internally consistent with the parameter values for the properties of anhydrous silicate melt reported by Lange and Carmichael (1987, 1990). The model calculation developed in this study reproduces the experimentally determined densities of various hydrous melts, and can be used to calculate the relationships between pressures, temperatures, and H2 O concentrations of various hydrous melts from ultramafic to felsic compositions at pressures of 0–4.29 GPa. Using the new parameter set, we investigate the effects of H2 O content on the seismic velocity of hydrous melts, as well as seismic velocities in partially molten regions of subduction zones. The results show that water content in silicate melt plays a key role in determining seismic velocity structure, and therefore must be taken into account when interpreting seismic tomography. Key Points: A model is proposed for the calculation of P‐V ‐H2 O relationships of hydrous melts up to 4.29 GPa Ideal mixing of H2 O and silicate melt accurately reproduces the P‐V relations of hydrous melts Water content in silicate melt must be taken into account when interpreting seismic tomography